2014
DOI: 10.4028/www.scientific.net/amm.566.134
|View full text |Cite
|
Sign up to set email alerts
|

Impact Compressive Properties of Foamed Film with Closed Cell

Abstract: The compressive properties of foamed polyethylene (PE) film with a closed cell for electronic devices have been investigated. A commercial closed cell foamed PE film with a density of 330 kg/m3 was used. Quasi-static testing was carried out at strain rates of 10−3 to 10−1 s−1. The strain rate of the impact test was approximately 105 s−1 by means of split Hopkinson pressure bar method. Within the set of experiments, the compressive stress increased with the strain rate in both the quasi-static and impact test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, in spite of same material and same thickness, the difference of flow stress appears in each specimen. As in our previous study [2][3][4], a plateau deformation was observed immediately after compression without the elastic response in the foamed PE film. However, in the spheral type specimen, elastic response was observed.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…However, in spite of same material and same thickness, the difference of flow stress appears in each specimen. As in our previous study [2][3][4], a plateau deformation was observed immediately after compression without the elastic response in the foamed PE film. However, in the spheral type specimen, elastic response was observed.…”
Section: Resultssupporting
confidence: 80%
“…Second, the impact compressive test was performed using the split Hopkinson pressure bar (SHPB) method established by Kolsky [5][6][7] at a strain rate of over 10 3 s −1 . In the previous study [2][3][4], we proposed that the transmitted bar have a smaller cross-sectional area, and a lower elastic modulus indicated the high sensitivity of the load measurements of the specimens. In addition, an attempt was made to obtain high sensitivity measurements of the incident stress wave using an incident bar with a flange [2].…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations